Application of the Health Belief Model to Predict Iron Supplementation Compliance Among Adolescent Girls in Bantul, Indonesia - Thami Septiariyani; Retno Heru Setyorini; Teguh Budi Prasetya (Media Publikasi Cendekia Indonesia, 2026)
Anemia remains a major public health problem among adolescent girls in low-income countries, leading to long-term consequences such as decreased academic performance and increased risks during future pregnancies. Although iron supplementation programs have been widely implemented in schools, adherence among adolescent girls remains low. This study aimed to identify factors associated with compliance with iron supplementation among teenage girls using the Health Belief Model (HBM) framework. A cross-sectional study was conducted from February to June 2024 in Bantul Regency, Yogyakarta Special Region, Indonesia. Data were collected from 230 adolescent girls using a structured questionnaire. Bivariate analysis was performed using the Chi-square test, followed by multivariate logistic regression to identify independent predictors of compliance. The 230 participants, only 49.5% adhered to iron supplementation. Most respondents reported low perceived benefits (62.6%) and low perceived health threats (66.7%). Bivariate analysis showed significant associations between perceived benefits, perceived health threats, and perceived barriers with compliance (p<0.001). However, multivariate analysis identified perceived health threats (p=0.004; AOR = 3.52; 95% CI: 1.48–8.38) and perceived barriers (p<0.001; AOR = 7.11; 95% CI: 3.26–15.51) as independent predictors of compliance. Compliance with iron supplementation among adolescent girls is significantly influenced by perceived health threats related to anemia and perceived barriers to tablet consumption. Interventions should focus on increasing risk awareness and reducing perceived barriers through targeted education, supportive school environments, and multisectoral engagement to enhance anemia prevention efforts.